Active power reserve photovoltaic virtual synchronization control technology - Xing Zhang (Chinese Journal of Electrical Engineering, 2020)
The photovoltaic virtual synchronous generator (PV-VSG) solves the problem of lack of inertia in the PV power-generation system. The existing PV plants without energy storage are required to participate in the power grid's frequency modulation (FM), but existing PV-VSGs with energy storage have high requirements for coordinated control. Therefore, the active power reserve PV-VSG (APR-PV-VSG) is studied. Based on the different methods to obtain the maximum power point (MPP), the peer-to-peer and master-slave APR-PV-VSG strategies are proposed. The PV inverters are deviated from the MPP to reserve active power, which is used as the virtual inertia and primary FM power. These methods equip the PV power station with FM capability. The effectiveness of the proposed control strategies is verified by simulation results.